2017
DOI: 10.5334/irsp.15
|View full text |Cite
|
Sign up to set email alerts
|

When, How and Why is Loss-Framing More Effective than Gain- and Non-Gain-Framing in the Promotion of Detection Behaviors?

Abstract: This short paper aims to untangle the effect of loss-framing versus gain and non-gain; explaining when, how and why it influences individuals' intentions to engage in cholesterol screening. We argue that framing-effects are (1) significant only when individuals perceive the issue to be highly relevant and (2) are mediated by perceived negative consequences (resulting from undergoing the test) and response-efficacy. In a 2(issue-relevance: high vs low) × 3(framing: gain vs non-gain vs loss) experiment, 229 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Meta-analyses show that framing does not affect detection behaviours, such as attending screening appointments [49, 50]. Some research suggests that the effect of framing on health detection behaviours is moderated by individuals’ perception of their personal risk [49, 51, 52], and patients may not have perceived cardiovascular disease to be of high personal relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses show that framing does not affect detection behaviours, such as attending screening appointments [49, 50]. Some research suggests that the effect of framing on health detection behaviours is moderated by individuals’ perception of their personal risk [49, 51, 52], and patients may not have perceived cardiovascular disease to be of high personal relevance.…”
Section: Discussionmentioning
confidence: 99%
“…This internalization should be more evident in Indonesia since, compared to their Chinese counterparts, Indonesian students are indoctrinated more strongly on collective-orientation regarding family values, security, conformity, achievement, motivation, performance-approach and performance-avoidance goals (Liem and Nie 2008). Bosone and Martinez' (2017) found that anticipated loss is stronger than behavioral anticipated gain. Proponents' anticipated distress can be aligned with anticipated loss and proponents' anticipated joyfulness with anticipated gain.…”
Section: Discussionmentioning
confidence: 96%
“…However, the influence of other people's anticipated emotions on self-efficacy is still absent from recent studies. Fortunately, Bosone and Martinez's (2017) work can be used as a starting point. They said that when framed with future gains, people show no increase in creativity efficacy.…”
Section: Mediating Effect Of Self-efficacymentioning
confidence: 99%
“…In the gain and lose scenario, schadenfreude can be viewed as lose and the condition of being envied situation as gain. Bosone and Martinez (2017) revealed that framing individuals with a loss would increase self-efficacy. We can understand this finding from Roger's selfprotection theory (Alicke & Sedikides, 2009;Rogers, 1975) which specifies that individuals will increase their self-efficacy when confronted with fear or threat.…”
Section: Rivals' Anticipated Emotions and Self-efficacymentioning
confidence: 99%
“…P7: Rivals' joyfulness, anticipated as a response to individuals' competitive position decrease, increases self-efficacy. Bosone and Martinez (2017) further stated that framing with gain has a weak effect on efficacy belief. The scenario of being envied positions students as the winner or high efficacy people that require no additional effort to cover the weakness.…”
Section: Rivals' Anticipated Emotions and Self-efficacymentioning
confidence: 99%